2021
DOI: 10.1021/acscentsci.1c00110
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Patterning during Frontal Polymerization

Abstract: Complex patterns integral to the structure and function of biological materials arise spontaneously during morphogenesis. In contrast, functional patterns in synthetic materials are typically created through multistep manufacturing processes, limiting accessibility to spatially varying materials systems. Here, we harness rapid reaction-thermal transport during frontal polymerization to drive the emergence of spatially varying patterns during the synthesis of engineering polymers. Tuning of the reaction kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 44 publications
3
72
0
Order By: Relevance
“…Frontal polymerization was originally discovered by Chechilo and Enikolopyan in the 1970s 11–14 and then independently rediscovered by Pojman in the early 1990s 15–21 . Since its discovery, FP research has been extended to other areas such as deep eutectic solvents, 22–25 hydrogels, 26 ROMP, 27,28 gradient materials 29 and cationic‐initiated polymerization 30–35 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontal polymerization was originally discovered by Chechilo and Enikolopyan in the 1970s 11–14 and then independently rediscovered by Pojman in the early 1990s 15–21 . Since its discovery, FP research has been extended to other areas such as deep eutectic solvents, 22–25 hydrogels, 26 ROMP, 27,28 gradient materials 29 and cationic‐initiated polymerization 30–35 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Frontal polymerization was originally discovered by Chechilo and Enikolopyan in the 1970s [11][12][13][14] and then independently rediscovered by Pojman in the early 1990s. [15][16][17][18][19][20][21] Since its discovery, FP research has been extended to other areas such as deep eutectic solvents, [22][23][24][25] hydrogels, 26 ROMP, 27,28 gradient materials 29 and cationicinitiated polymerization. [30][31][32][33][34][35] Charge transfer complexes (CTCs) are a potential replacement for peroxide-based initiators and have been shown to act as dual thermal and photoinitiators.…”
Section: Introductionmentioning
confidence: 99%
“…33 The ultimate objective of this work is to harness these thermal instabilities by changing the process conditions through the tuning of the reaction and thermal transport, leading to spontaneous and controllable patterns and spatially dependent morphological, chemical, optical, and mechanical properties in the polymer. 34 The numerical and experimental study presented hereafter has two main goals: (1) to investigate how the introduction of microparticles with a melting temperature below the front temperature affects the front velocity and temperature in the FP of cyclooctadiene (COD) through the conversion of some of the reaction heat into energy absorbed by the phasetransforming microparticles; and (2) to show how the amplitude and wavelength of FP-driven thermal instabilities can be tuned by the presence of phase-transforming microparticles, thereby providing a potential methodology to achieve patterning in thermoset polymers and composites. Poly-(caprolactone) (PCL) with a combination of proper melting point ∼60 °C, large melting enthalpy 139 J/g, and high compatibility with the COD is expected to interact with the polymerizing front effectively and hence selected as the demonstrative phase-transforming material in the present study.…”
Section: ■ Introductionmentioning
confidence: 99%
“…I n this issue of ACS Central Science, Lloyd et al have shown how to use some unique characteristics of frontal polymerization to create mechanical, chemical, morphological, and optical patterns spontaneously. 1 They have created systems whose properties can be tuned spatially by adjusting the initial conditions of a self-propagating polymerization reaction. What makes this work so exciting is that the macroscopic property variations were achieved without the need for masks, molds, or printers that are used in traditional manufacturing.…”
mentioning
confidence: 99%
“…In this issue of ACS Central Science , Lloyd et al have shown how to use some unique characteristics of frontal polymerization to create mechanical, chemical, morphological, and optical patterns spontaneously . They have created systems whose properties can be tuned spatially by adjusting the initial conditions of a self-propagating polymerization reaction.…”
mentioning
confidence: 99%